Experimental Study on Bioclogging in Porous Media during the Radioactive Effluent Percolation - Rong Gui; Yu-xiang Pan; De-xin Ding; Yong Liu; Zhi-jun Zhang (Advances in Civil Engineering)
The sand columns inoculated with the indigenous microorganism (Aspergillus niger) were used to investigate the effect of bioclogging during the radioactive effluent percolation. The hydraulic gradient, volumetric flow rate, and uranyl ions concentration were monitored over time. The sand columns were operated with continuous radioactive effluent of uranium tailings reservoir. After 68 days, the hydraulic conductivity of the sand columns decreased more than 72%, and the adsorption rate of uranyl ions by Aspergillus niger reached more than 90%. Environmental scanning electron microscope imaging confirmed the biofilm covering the surface of sand particles and connecting sand particles together, which resulted in a reduction of hydraulic conductivity. The results indicated that the propagation of Aspergillus niger can clog the seepage channel and effectively adsorb the uranyl ions of radioactive effluent in the porous media, which provides a suitable measure for controlling the migration of radioactive effluent of uranium tailings reservoir into the subsurface environment.